Discourse features in the lyrics of the Tamil song 'Annaiyin Karuvil' - Perumal, Thanalachime; Muthusamy, Paramasivam; Salleh, Che Ibrahim; Krishnamoorthy, Karunakaran (Universiti Putra Malaysia Press, 2015)
This study is an attempt to analyse the Tamil movie song, 'Annaiyin Karuvil', meaning 'mother's womb' from the Tamil movie 'Haridass'. This song is one of the popular motivational songs of a Tamil lyricist, called Annamalai. The texture discourse of this song will be analysed in terms of grammatical and lexical usages found by making use of discourse analysis.